Comparing and Quantifying Indoor Performance of Organic Solar Cells. Issue 34 (21st July 2021) - Lübke, Dana; Hartnagel, Paula; Angona, Johanna; Kirchartz, Thomas
Abstract: With increasing efficiencies of non‐fullerene acceptor‐based organic solar cells, thin‐film technology is becoming a promising candidate for indoor light harvesting applications. However, the lack of standardized comparison methods makes it difficult to quantify progress and to compare indoor performance. Herein, a simple method to calculate the efficiency of solar cells under any possible light source and illuminance with only using simple standard measurements (current–voltage curves and quantum efficiency) is presented. Thereby, equal evaluation conditions are ensured, so that indoor solar cells can be ranked and compared according to their efficiency. Efficiencies are shown to typically vary by ±20% when using different different light emitting diode spectra with color temperatures ranging from 2700 to 6500 K. Calculations based on a detailed balance model indicate that the optimal bandgap of the absorber material depends on the used light source and ranges between 1.75 and 2 eV. The approach is validated by comparison with literature data and many calculated efficiencies match well with experimental data obtained with a specific light source. However, some reported efficiencies cannot be reproduced with the model, which highlights the need to reassess low light measuring techniques. Furthermore, a script is provided for use by the community. Abstract : Although organic photovoltaics have been established to be a promising candidate for indoor light recycling, standardized testing conditions to quantify their performance are still lacking. Therefore, a method to calculate the efficiency of solar cells on the basis of relative emission spectra, quantum efficiency and current‐density‐voltage measurements, which enables a fair ranking of champion solar cells, is proposed.